PENENTUAN KUANTITAS MAHAR DAN ‎UANG HANTARAN MENURUT PERSPEKTIF ‎HUKUM ISLAM DAN ADAT MASYARAKAT ‎TANJUNGBALAI - Nasution, Irwansyah Putra (Jurnal Ushuluddin, 2021)
AbstractIn the community, dowry is the main discussion when preaching the bride-to-be, even though the original law of this dowry or dowry isn’t mandatory or mubah, even though dowry is basically mandatory from dowry, and in the city community in particular is more concerned or prioritizes dowry than dowry, so that the value of dowry is smaller than dowry. This research was written using a qualitative method, meaning that the research aims to understand every phenomenon experienced by individuals, such as behavior, perception, motivation, action, and others. The position of customary money based on the results of the author's research is one of the absolute conditions that must be done because customary money is a mandatory gift that must be given by the man to the woman who will be used as capital for the wedding party. A review of Islamic law on customary money explains that there is no provision that regulates customary money in Islam, the law is mubah because there is no evidence that prohibits it, the law of giving customary money according to Islam is mubah, but if it is included in the custom, then the law is mandatory, because there are rules in Islamic law